Using Visual And auditory Teaching Aids And Their Effect On Learning Scoring Accuracy in Youth Football Players Aged (17 – 18) Years Old - Mohameed, Saher (Journal of Physical Education, 2017)
The aim of the research is to identify the effect of visual and auditory teachingaids and their effect on learning the accuracy of scoring in football for players aged 17 – 18years old. The researcher used the experimental method. The subjects were (24) Al Anbarfootball team that was divided into two groups; the experimental group and the controllinggroup. The experimental group used visual and auditory aids to learn scoring in footballwhile the controlling group used the traditional curriculum. The researcher concluded thatthe experimental group surpassed the controlling group in learning scoring in football.